Styles of Leadership, Fears of Compassion, and Competing to Avoid Inferiority - Basran, Jaskaran; Pires, Claudia; Matos, Marcela; McEwan, Kirsten; Gilbert, Paul (Frontiers in Psychology, 2019)
There is general agreement that styles of leadership evolved from mammalian group living strategies that form social ranks. In both non-human primates and humans, different styles of hierarchical dominant-subordinate and leader-follower behavior can be observed. These can be described in terms of dimensions of antisocial (relatively self-focused, aggressive and threat-based) and prosocial (relatively empathic, caring, and supportive) interpersonal styles. The aim of this study was to explore how a set of established self-report questionnaires might relate to these two dimensions. Two hundred and nineteen students completed questionnaires assessing ruthless self-advancement, coalition building, and dominant leadership styles, as well as hypercompetitiveness, narcissism, striving to avoid inferiority, compassion focused and ego focused goals, fears of compassion, social safeness and attachment (in)security. A principal component analysis supported an antisocial leadership style factor which comprised of ruthless self-advancement, narcissism and hypercompetitiveness. This was significantly correlated with fears of compassion, ego focused goals, insecure striving (striving to avoid inferiority), fears of losing out, fears of being overlooked, fears of being rejected, and avoidant relating in close relationships. It was significantly negatively correlated with compassionate goals. As the results did not reveal a clear factor solution for a prosocial leadership style, we chose to use the coalition building leadership style variable. This showed the opposite pattern, being significantly negatively correlated with narcissism, hypercompetitiveness, fears of compassion, fears of active rejection, and avoidance in close relationships. It was significantly positively correlated with secure striving, compassionate goals, and social safeness. We also found that fears of compassion for others was a partial mediator of the relationship between insecure striving with antisocial leadership style. Moreover, lower fears of compassion for the self emerged as a key mediator for the relationship between non-avoidant attachment with coalition building leadership style and, secure non-striving with coalition building leadership style. While the motive to accumulate social power, resources and dominance may be linked to antisocial forms of leadership, the intensity of the drive may also be linked to unaddressed threats and fears of rejection and fears of compassion. Efforts to promote more ethical, moral and prosocial forms of leadership may falter if such fears are left unaddressed.